Hygienisation, Gentrification, and Urban Displacement in Brazil. Issue 1 (24th October 2019) - Garmany, Jeff; Richmond, Matthew A.
Abstract: This article engages recent debates over gentrification and urban displacement in the global South. While researchers increasingly suggest that gentrification is becoming widespread in "Southern" cities, others argue that such analyses overlook important differences in empirical context and privilege EuroAmerican theoretical frameworks. To respond to this debate, in this article, we outline the concept of higienização (hygienisation), arguing that it captures important contextual factors missed by gentrification. Hygienisation is a Brazilian term that describes a particular form of urban displacement, and is directly informed by legacies of colonialism, racial and class stigma, informality, and state violence. Our objective is to show how "Southern" concepts like hygienisation help urban researchers gain better insight into processes of urban displacement, while also responding to recent calls to decentre and provincialise urban theory. Resumo: Este artigo dialoga com debates recentes sobre a gentrificação e o deslocamento no Sul global urbano. Enquanto pesquisadores urbanos sugerem cada vez mais que a gentrificação está crescendo nas cidades do Sul global, outros argumentam que essas análises ignoram importantes diferenças no contexto empírico dessas cidades, e privilegiam a teoria Euro‐Americana. Para responder a esse debate, esboçamos o conceito de higienização, argumentando que ele captura fatores contextuais importantes que são perdidos quando análises são feitas a partir do conceito de gentrificação. Higienização é um termo brasileiro que descreve uma forma particular de deslocamento e é diretamente informado por legados de colonização, estigma social e racial, informalidade, e violência do Estado. Nosso objetivo é mostrar como conceitos como higienização, enraizados no contexto do Sul global, ajudam os pesquisadores urbanos a melhor entender os processos de deslocamento, enquanto também responde a recentes intervenções exigindo a descentralização e provincialização da teoria urbana.